Mapping audience engagement of cultural organizations - Jurėnė, Skaistė; Krikščiūnienė, Dalia (Vilnius University Open Series, 2019)
Audience engagement is a new strategic approach of cultural organizations when they aim to turn audience members to active participants and thus build their personal relationships with the organization. There are various suggestions how to make audience engagement stronger, but lack of evidence how to monitor it. In this article, we introduce integrated approach to audience engagement while evaluating and analysing the concept of mapping. The created prototype of audience engagement mapping can help cultural organizations to efficiently measure and evaluate their actions for choosing effective audience engagement measures. The empirical part of the article includes a study of 18 cultural organizations of Kaunas city. The study revealed numerous gaps among the theoretical recommendations and practical approaches of the organizations. In practice, the organizations tend to pay attention to the online activities, especially for affecting accessibility and cognition, however, there is lack of collective creation and audience involvement and engagement into programme development, discussions and context expansion.